Austenite stabilisation by two step partitioning of manganese and carbon in a Mn-TRIP steel. Issue 17 (22nd November 2019) - Du, P. J.; Yang, D. P.; Bai, M. K.; Xiong, X. C.; Wu, D.; Wang, G. D.; Yi, H. L.
ABSTRACT: In addition to manganese, carbon partitioning has been proposed in a new medium Mn-TRIP steel by two-step partitioning during the first batching annealing and the final continuous annealing. In the second-step partitioning, the cementite dissolves and blocky austenite forms with carbon enrichment, while the partition of manganese is negligible from prior lath austenite back into ferrite due to short duration. The combined partition of carbon and manganese improves both fraction and stability of retained austenite. The alloy has exhibited the product of strength and elongation of approximately 50 GPa%. It is highlighted that there is no Lüder strain in tensile curves. The microstructure evolution and relationship of microstructure and properties have been investigated and characterised carefully in this research. This paper is part of a Thematic Issue on Medium Manganese Steels.